Social Integration through the Prism of Social Inclusion - Pavlencu, Mariana (Acta Universitatis Danubius. Administratio, 2022)
Social inclusion refers to respecting the status and rights of all people in a society, who must have the opportunity to participate in its life in a relevant way and enjoy equal treatment with others. Social inclusion is a process that provides people at risk of poverty and social exclusion with the necessary opportunities and resources to fully participate in the economic, social and cultural life of society, ensuring them a standard of living considered decent in the society in which they live. The social inclusion research process must take into account that forms of exclusion are interdependent and therefore the exclusion of a person or group in one area could lead to exclusion in other areas. The ultimate goal of social inclusion is to guarantee the integration of each individual into society, regardless of the presence of limiting elements.